2020
DOI: 10.1186/s12879-020-05434-4
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical presentations of two renal transplant recipients with coronavirus disease 2019: a case report

Abstract: Background The Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome Coronavirus-2 has spread rapidly worldwide and disease spread is currently increasing. Data on the clinical picture of transplant recipients and management of the anti-rejection immunosuppressive therapy on COVID-19 infection are lacking. Case presentation We report two cases of COVID-19 infection in renal transplant recipients with variable clinical presentations. The first patient presented with mild respiratory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…1 . Most included studies were case reports (n=89) [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ...…”
Section: Resultsunclassified
“…1 . Most included studies were case reports (n=89) [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ...…”
Section: Resultsunclassified
“…A total of 178 studies were found to have reported IFNα treatment for COVID-19 (Supplemental 2). [13] , [17] , [19] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , …”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsunclassified
“…The use of IFNα inhalation was reported in patients with various comorbidities and conditions, including patients with atopic dermatitis, [38] allergic rhinitis, [38] bronchiolitis, [25] chronic obstructive pulmonary disease, [84] , [162] tuberculosis, [55] cardiovascular disease, [22] hypertension, [22] , [84] , [150] , [162] diabetes, [32] , [39] hyperlipidemia, [150] obesity, [126] metabolic syndrome, [192] chronic hepatitis B infection, [76] , [153] chronic kidney disease, [22] , [70] malignancy, [163] liver transplant, [50] kidney transplant, [70] , [172] and pregnancy. [19] The use of subcutaneous injection of IFNα was reported in patients with diabetes, [42] hypertension, [42] , [44] hyperlipidemia, 42 chronic hepatitis B infection, [140] primary myelofibrosis with macrocytic anemia, [44] dementia, [44] chronic kidney disease, [44] Behcet's disease, [190] and osteoporosis.…”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsmentioning
confidence: 99%
“…It may have a severe clinical course, while some patients may experience no significant clinical symptoms (2). Severe lung damage and other complications that lead to organ failure in COVID-19 could result from a dysregulated immune system response (3).…”
Section: Introductionmentioning
confidence: 99%